Последняя из рода Тюдор - Грегори Филиппа (Любовь королей, 2019)
Экземпляры: ф7 (20230209) / Инвентарный номер: 64278 / Цена: 262.00 / Сис.шифр: И(англ) / Авт.знак: Г 79 / ГРНТИ: 17.82.31 / ББК: 84(4Вел)